2011
DOI: 10.1080/13632434.2010.540560
|View full text |Cite
|
Sign up to set email alerts
|

Tensions in leadership development: head teachers' experience in North Cyprus

Abstract: Leadership development has been an area of much research, particularly in the last two decades. This has been mirrored by increased policy activity to build leadership capacity in schools through preparation programmes and continuing professional development. This article examines continuing professional development provision for head teachers in the context of North Cyprus. Findings demonstrate a widespread dissatisfaction among head teachers of the existing provision relating to policy orientations guiding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Instead, the findings suggest that a procedure based on trial and error operates and head teachers are tested on the job. This is in stark contrast to the policy now evident in many nations, which have approached the preparation and development of head teachers more systematically than was previously the case (although it is still possible to come across national contexts where leadership preparation and development is underdeveloped (Mertkan, 2011)). When appointed for the first time, head teachers are designated as a candidate head teacher for a year and those found successful once their candidacy is reviewed receive a permanent appointment.…”
Section: Findings and Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Instead, the findings suggest that a procedure based on trial and error operates and head teachers are tested on the job. This is in stark contrast to the policy now evident in many nations, which have approached the preparation and development of head teachers more systematically than was previously the case (although it is still possible to come across national contexts where leadership preparation and development is underdeveloped (Mertkan, 2011)). When appointed for the first time, head teachers are designated as a candidate head teacher for a year and those found successful once their candidacy is reviewed receive a permanent appointment.…”
Section: Findings and Discussionmentioning
confidence: 68%
“…Within this framework, school leadership is linked to educational reform, school improvement and organisational change (Bush, 2008b;Rhodes and Brundrett, 2009) where the work of head teachers is intensified and diversified to include both organisational capacity, building with elements of pedagogical leadership and leadership development in others, and business management with elements of financial management, human resource management and site management (Crow, 2007;Gronn, 2003b;Mertkan, 2011). Headship has become extremely complex over the past two decades in particular and head teachers have been increasingly pressured to deliver more at a faster pace and to work longer hours.…”
Section: Introductionmentioning
confidence: 99%
“…Michaelidou and Pashiardis (2009) Responses of Cypriot principals in previous studies show that the first years of principalship was a matter of sink or swim as there was no formal preparation for the principals (Pashiardis & Ribbins, 2003), apart from more than ten years of teaching experience for appointments to headship (Mertkan, 2011). There are now short courses for the newly appointed principals.…”
Section: Preparation For Principalshipmentioning
confidence: 99%
“…Programme participants also called for more context-based learning, based on their own school contexts, rather than studying in high performing or 'famous schools'. This relates to the assumption that leadership happens in context, therefore learning should relate to the particular setting and needs of each school and to the characteristics of each school leader(Kelly and Saunders 2010;Mertkan, 2011). Some participants suggested that, instead of learning what happened in those successful and high performing schools, they should like to address issues in their own schools.…”
mentioning
confidence: 99%
“…Proportion, preferences and gaps among delivery approachesThe main criticism of this approach is that leadership happens in context, therefore it should be learned in respect of the particular setting and needs of each school (Hess andKelly, 2007, Kelly andSaunders 2010;Mertkan, 2011). Four of the interviewed principals argued that it takes time to digest, absorb and transferorm the knowledge given through lectures (P1, P4, P5 and P9).…”
mentioning
confidence: 99%